2017
DOI: 10.3892/br.2017.916
|View full text |Cite
|
Sign up to set email alerts
|

Association of nitric oxide synthase 3 gene polymorphism with the risk of type 2 diabetes

Abstract: Abstract. Type-2 diabetes (T2D) is a multifactorial (environmental and genetic factors) and global epidemic disease with an estimated high prevalence worldwide. Studies have indicated that nitric oxide synthase 3 (NOS3) has several important roles in the pathogenesis of T2D. The present study aims to investigate the association between NOS3 rs1800779(A/G) and T2D in an Iranian sample population. A case-control study was conducted on 250 T2D patients and 250 healthy control subjects (HCs). Genotyping of the rs1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…These frequencies range from 4 to 82%. Several of these genes have been previously identified in association with other diseases [35,36]. Of the variants previously identified, missense variants are reported in eight genes.…”
Section: Resultsmentioning
confidence: 99%
“…These frequencies range from 4 to 82%. Several of these genes have been previously identified in association with other diseases [35,36]. Of the variants previously identified, missense variants are reported in eight genes.…”
Section: Resultsmentioning
confidence: 99%
“…Garme et al . (2017) reported that the AA genotype of rs3918188 SNP of NOS3 gene, may cause an individual to be more susceptible to develop T2DM 53 . Zhao et al .…”
Section: Discussionmentioning
confidence: 99%
“…For genotyping the eNOS rs1800779 polymorphism, the ARMS-PCR test was used. The primers were taken from previously published literature 23 ( Table 3 ). First, 2 μL of genomic-extracted DNA, 10 μL of Taq DNA Polymerase 2× Master Mix RED (Ampliqon, Danish), 1 μL of each forward (inner and outer) and reverse (inner and outer) primer, and 4 μL of nuclease-free water were used for a total of 20 μL.…”
Section: Methodsmentioning
confidence: 99%
“…The eNOS rs1800779 polymorphism has been considered to be related to migraine disorder 22 and type 2 diabetes mellitus (T2DM). 23 …”
Section: Introductionmentioning
confidence: 99%